Adição de enzimas em dietas com diferentes fontes de proteína para frangos - Fortes, Bruno Duarte Alves (2014)
Three experiments were perfomed in order to evaluate the addition of an enzymatic complex containing xylanase, amylase, and protease to rations with different protein sources for broilers through the true digestibility of amino acids, metabolization of nutrients and performance of animals. The first experiment was a completely randomized design with nine treatments and five replications. Birds were subjected to a five days adaptation period to experimental diets and the diets were as follows: one diet free of protein (DFP), and eight DFP diets with tested feedstuffs to replace corn starch. The true digestibility coefficient of essential amino acids, corn gluten meal (60%), soybean protein concentrate, bovine dried plasma and viscera meal were measured at seven and 21 days of age. The digestibility coefficient of essential amino acids at seven and 21 days of age were as higher (p<0.05) for the treatments with enzymatic complex and for the digestibility of essential amino acids the coefficients were higher (p<0.05), only at seven days of age, for corn gluten meal (60%), soybean protein concentrate and viscera meal. It was possible to conclude that the addition of xylanase, amylase and protease improved the digestibility of amino acids, regardless of the ingredient and the age of the animals. The second study was a metabolism experiment conducted to determine the coefficient of apparent metabolism of dry matter (CAMDM), crude protein (CAMCP), ether extract (CAMEE) and apparent metabolizable energy corrected for nitrogen balance (AMEn) of feed for broilers with different protein feedstuffs, such as corn gluten meal (60%), soybean protein concentrate, viscera meal and bovine dried plasma, associated with enzymatic complex. A completely randomized design with nine treatments (one reference diet, and eight diets with inclusion of tested feedstuffs with or without addition of enzymatic complex) and five replicates was used, with ten birds in the pre-starter diet and six birds in the initial diet. Tested feedstuffs replaced 40% reference diet. The use of enzymatic complex in pre-starter diets was effective (p<0.05) while improving CAMDM for soybean protein concentrate, CAMCP for soybean protein concentrate and bovine dried plasma and AMEn for bovine dried plasma. For the initial phase, only AMEn bovine dried plasma was affected (p<0.05) by the inclusion of xylanase, amylase and protease. The supplementation of xylanase, amylase and protease improved CAMDM and CAMCP in diets containing soybean protein concentrate as its main source of protein and CAMCP diets containing bovine dried plasma at seven days age, even more enzymatic complex was effective while increasing levels of apparent metabolizable energy corrected for nitrogen balance of diets containing bovine dried plasma. The third experiment was proposed to evaluate broiler performance using xylanase, amylase and protease in diets formulated with different protein ingredients. A completely randomized design with eight treatments and six replicates with 30 birds per cage was used. Treatments were as follows: T1- basal diet with 6% corn gluten meal (60%); T2- basal diet with 6% corn gluten meal (60%) and enzymatic complex; T3- basal diet with 6% soybean protein concentrate; T4- basal diet with 6% soybean protein concentrate and the enzymatic complex; T5- basal diet with 6% viscera meal; T6- basal diet with 6% viscera meal and the enzymatic complex; T7- basal diet with 5% bovine dried plasma; T8- basal diet with 5% bovine dried plasma and the enzymatic complex. No differences were observed (p>0.05) among treatments on feed intake throughout the experiment (1-42 days); however, weight gain, feed conversion and average weight of the birds were affected (p<0.05). Treatments with vegetable protein sources supplemented with enzymes produced an average reduction in the values of feed conversion and an increase in mean weight of 6.24 and 4.87% for diets containing corn gluten meal (60%) and 6.66 and 4.52% for diets containing soybean protein concentrate, respectively. Diets containing protein sources of animal origin and the inclusion of enzymatic complex (xylanase, amylase and protease) reduced the average values of feed conversion and increased the average weight: 5.88 and 4.57% for diets containing bovine dried plasma and 7.14 and 6.34% for diets containing viscera meal, respectively. The inclusion of enzymatic complex was effective while improving the average values for weight gain, feed conversion and average weight during 1-42 days of age.